Digital Inclusion for Educational Equity: An IT-Based Mentoring Program for KIP-K Scholarship Registration - Aji Saputra; Abdu Mas’ud; Sundari Sundari (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: Although the Kartu Indonesia Pintar Kuliah (KIP-K) program has been implemented since 2020, it continues to faces several challenges, especially in terms of socialization and information accessibility.Aims: This community service program aimed to support underprivileged students in accessing higher education through the KIP-K scholarship scheme.Methods: The activity targeted 12 eligible students at SMA Negeri 6 Ternate on May 21, 2025. The intervention consisted of two phases: (1) socialization and motivational sessions explaining KIP-K requirements and procedures, and (2) hands-on mentoring where students created accounts and uploaded documents via smartphones. A WhatsApp group was used for two weeks of follow-up, troubleshooting, and document collection. Program success was measured by account creation, completion of required data fields, and timely submission.Results: A total of 12 students (100%) successfully registered for KIP-K, completed the required data fields, and selected study programs. The WhatsApp group effectively facilitated real-time support, especially in gathering and uploading documents from home.Conclusion: This program effectively increased student motivation and digital literacy to register for KIP-K. Community-based digital mentoring has proven to be a practical approach to promoting access to higher education.